Advances in automation, signal processing, instrumentation, and control select proceedings of i-CASIC 2020 - Sivakumaran, N.; Hampannavar, Santoshkumar; Komanapalli, Venkata Lakshmi Narayana (Springer, 2021)
This book presents the select proceedings of the International Conference on Automation, Signal Processing, Instrumentation and Control (i-CASIC) 2020. The book mainly focuses on emerging technologies in electrical systems, IoT-based instrumentation, advanced industrial automation, and advanced image and signal processing. It also includes studies on the analysis, design and implementation of instrumentation systems, and high-accuracy and energy-efficient controllers. The contents of this book will be useful for beginners, researchers as well as professionals interested in instrumentation and control, and other allied fields.